1985
DOI: 10.1021/i300018a028
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mathematical modeling of isomerization of methyl linoleate on ruthenium catalyst. 1. Conjugation and hydrogenation

Abstract: extraction of the esterified product over the intact triglycerides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 3 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…The reaction kinetics were found to be further complicated by polymer formation at low solvent concentrations. The kinetics and mathematical modeling of isomerization of methyl linoleate on ruthenium on carbon were also reported by Mukesh et al (1985). It was observed that polymers form in the presence of small amounts of solvent and that isomerization and polymerization are parallel competing reactions.…”
Section: Heterogeneous Transition Metal Catalysis By Metal Particles ...mentioning
confidence: 85%
“…The reaction kinetics were found to be further complicated by polymer formation at low solvent concentrations. The kinetics and mathematical modeling of isomerization of methyl linoleate on ruthenium on carbon were also reported by Mukesh et al (1985). It was observed that polymers form in the presence of small amounts of solvent and that isomerization and polymerization are parallel competing reactions.…”
Section: Heterogeneous Transition Metal Catalysis By Metal Particles ...mentioning
confidence: 85%
“…2.2). On the other hand, the isomerization of methyl linoleate over heterogeneous catalysts has been reported earlier, and the catalysts applied were rhodium and ruthenium on activated carbon [32,33], as well as bimetallic supported ruthenium nickel catalysts [34].…”
Section: Conjugated Linoleic Acids As Health Promoting Agents: Their mentioning
confidence: 84%
“…15 A mechanism involving hydride transfer could also be operative. Hydride transfer from the solvent has been discussed in the literature 21 in the case of isomerization of methyl linoleate (the methyl ester of linoleic acid) on carbonsupported ruthenium catalyst. Moreover, hydride-transfer reactions, in which the olefin itself acts as a hydrogen donor, might take place on acidic catalysts in the case of hydrocarbons.…”
Section: Discussionmentioning
confidence: 99%